A new jumping spider species of the genus Maeota (Araneae: Salticidae: Euophryini), with new faunistic data of the tribe from Colombia (2016)
A new species of jumping spider of the genus Maeota (Salticidae), M. galeanoae sp. nov., is described and illustrated from the Caribbean state of Magdalena, Colombia. Additionally, the genus Anasaitis is recorded for the first time from Colombia, with the species A. canalis, from the department of Chocó. Moreover, new records are presented for Maeota serrapophysis from the departments of Magdalena, Quindío and Valle del Cauca, Colombia, with individuals from the southern region presenting a slightly different pattern of coloration in which the prosoma, abdomen and legs have a reticulated brown and gray pattern. New faunistic data from Colombia are also presented for the species M. betancuri and Ilargus galianoae. Finally, a distribution map is presented, including new and previously published records for the taxa treated here.